Analisis Efisiensi Pemasaran Ayam Ras Pedaging (Broiler) (Studi Kasus: Kecamatan Gunung Malela Kabupaten Simalungun) - Rindi Eka Prastiwi; Retna Astuti; Faoeza Hafiz Saragih (Jurnal Ilmiah Pertanian ( JIPERTA), 2020)
The purpose of this research is to know the marketing channel of broiler and to know the level of marketing efficiency of broiler in Gunung Malela Regency, Simalungun. This research is conducted from May to June 2017. This research uses sampling method by way of method of disproportionate stratified random sampling. Thesample of this research was 29 sample which are independent farmers, plasma farmers, partner companies, wholesalers and small traders.Based on the result of the research, there are two pattern of marketing channel of broiler which broiler in the first channel started from independent farmers to big traders to small pedgang and on second channel started from plasma farmers to partner companies, big traders to small traders. The marketing margin of broiler chicken on channel I is bigger compared to marketing channel II which is Rp 6,075 / kg. Channel marketing channels on channel I more efficient that is 0.01% and 0.04%.